THE LOCAL VALUE OF BADONCEK FOR POLITENESS ASPECT IN MINANG COMMUNITIES WEST SUMATRA - Muhammad Fauzi; Novita Sari (Universitas Islam Sumatera Utara (UISU), 2018)
This study analysis talking about the local value of Communication is the important thing in humanities sociality. The main part of the sociality life. Nowadays, doing communication is strongly influenced by the culture when communication is stated. This paper discusses on the relationship politeness strategy and Minang culture in doing communication. The Minang here was limited in the badoncek from wedding ceremony in Minang culture is a spontaneous social action and suitable with the needs of the moment. Indeed, the theory that used in politeness strategy was taken from Brown and Levinson theory. This theory was elaborated become four types of politeness strategy. They are bald on strategy, positive strategy, negative strategy, and off record strategy. The prior aim in this paper is to describe what types of politeness strategy that used in Minang wedding ceremony in their social life and to elaborate the types of politeness strategies applied by qualitative research.